Open Innovation and Eco-Innovation: Dynamic Capabilities for Improving SME Performance (GESTIÓN Y TENDENCIAS, 2021)
Enabling small and medium-sized enterprises (SMEs) to be competitive is no simple challenge; there are a number of constraints they must overcome. We therefore study a set of 684 Mexican SMEs using a structural equation model in order to determine the effects that developing open innovation and eco-innovation capabilities has on corporate performance.
Keywords: open innovation; eco-innovation